2018
DOI: 10.1186/s40594-018-0138-z
|View full text |Cite|
|
Sign up to set email alerts
|

Is the undergraduate microbiology curriculum preparing students for careers in their field?: an assessment of biology majors’ conceptions of growth and control of microorganisms

Abstract: BackgroundWe present an analysis of students’ responses to application-based questions on the topic of growth and control of microorganisms, from a questionnaire administered to 348 second and third year students of an Indian university who were enrolled in its undergraduate programs in Biotechnology or Microbiology. We examined aspects of the laboratory practice as reported by teachers and of the university assessment patterns that may explain our findings. Reports by teachers also included their views on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the students’ unpreparedness to use microbiology as guide for management of clinical scenarios using antibiotics highlights the gaps in their understanding of microbiology and its function in antimicrobial stewardship. A study in India showed a gap in the understanding of the microbiology career, and therefore the students, though they had career aspirations, were not prepared for them [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the students’ unpreparedness to use microbiology as guide for management of clinical scenarios using antibiotics highlights the gaps in their understanding of microbiology and its function in antimicrobial stewardship. A study in India showed a gap in the understanding of the microbiology career, and therefore the students, though they had career aspirations, were not prepared for them [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article (Sawant et al, 2018), a typesetting mistake was reported. The explanation of part labels d and e have been omitted from the caption of Fig.…”
Section: Correction To: International Journal Of Stem Education (2018mentioning
confidence: 99%
“…Employers are currently looking for and recruiting graduates with skills capable of providing solutions to human problems, reducing human efforts, saving space and time elapsed in the course of providing accurate results to contemporary issues. In Nigeria, in particular, a critical look at the undergraduate Microbiology curricula of most universities suggests an urgent need to reform the curricula and embark upon project designing intervention courses that improve competence [ 5 ]. As such, a university graduate with good microbiology results but no additional skills may remain jobless or employed with less pay than a non-graduate with necessary skills to meet the requirements of the recruiting organization.…”
Section: Introductionmentioning
confidence: 99%